Pengenalan Building Information Modeling (BIM) sebagai Jembatan Karir Arsitektur dan Konstruksi Masa Depan - Megawati, Puan Jati; Viriezky, Viata; Adrian, Ahmad Baqir; Seprianto, Tri (Nemui Nyimah, 2025)
Technological developments in the Business and Industry World (DUDI) require graduates of education, especially in the fields of construction and architecture, to have adequate digital competencies in order to compete globally. One of the technologies that is increasingly needed in industrial construction is Building Information Modeling (BIM), which enables the design, analysis, and management processes of projects in an integrated manner. However, BIM learning at the Vocational High School (SMK) level is still limited, both in terms of information access and device infrastructure. As part of the Tri Dharma of Higher Education, the University of Lampung through a team of lecturers from the Department of Architecture implemented a Community Service (PkM) program in the form of BIM socialization to class XI students of the Building Design, Modeling and Information Department (DPIB) at SMK Negeri 2 Bandar Lampung. This activity began with a discussion and coordination with the school to understand student needs and the achievement of expected competencies. Furthermore, an interactive socialization was carried out which included an introduction to the concept of BIM, its benefits in industrial construction, and basic practices using related software. The results of the activity showed an increase in students' understanding of the BIM concept, which was marked by high enthusiasm in the discussion session and positive responses through interactive quizzes and word clouds. With this program, it is hoped that students will gain new insights into the importance of BIM technology as a relevant skill for careers in the world of construction and architecture.